2015
DOI: 10.1111/jeu.12250
|View full text |Cite
|
Sign up to set email alerts
|

The Ultra‐Structural Similarities between Cryptosporidium parvum and the Gregarines

Abstract: Using a transmission electron microscopy-based approach, this study details the striking similarities between Cryptosporidium parvum and the gregarines during in vitro axenic development at high ultra-structural resolution. C. parvum zoites displayed three unusual regions within uninucleated parasites: epimerite-like, protomerite-like, and the cell body; these regions exhibited a high degree of morphological similarity to gregarine-like trophozoites. The presence of a mucron-like bulging structure at the side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…This is reflected in the new classification proposed by Cavalier-Smith [21] where Cryptosporidium, which is the only gregarine parasitic in vertebrates, has been placed in a class of its own. [6,14,17,20], and a greater degree of pleomorphism than reported previously, particularly of gamonts and gamont-like stages [11,20,21,26], all of which are gregarine characteristics. Of particular significance are observations from both in vitro and in vivo studies that, in addition to epicellular multiplication, Cryptosporidium can also complete its life cycle without apparent epicellular attachment with host cells (Figure 1, Key Figure) [6][7][8]10,12,18,20].…”
Section: Life Cyclementioning
confidence: 65%
See 2 more Smart Citations
“…This is reflected in the new classification proposed by Cavalier-Smith [21] where Cryptosporidium, which is the only gregarine parasitic in vertebrates, has been placed in a class of its own. [6,14,17,20], and a greater degree of pleomorphism than reported previously, particularly of gamonts and gamont-like stages [11,20,21,26], all of which are gregarine characteristics. Of particular significance are observations from both in vitro and in vivo studies that, in addition to epicellular multiplication, Cryptosporidium can also complete its life cycle without apparent epicellular attachment with host cells (Figure 1, Key Figure) [6][7][8]10,12,18,20].…”
Section: Life Cyclementioning
confidence: 65%
“…Table I summarizes the features that Cryptosporidium shares with gregarines. There are striking similarities both structurally and in feeding behavior between Cryptosporidium and gregarines [11,14,20,26]. Conversely, Cryptosporidium is unusual compared with other gregarines with regard to its diverse and broad host range and its close association with the host cell, which is epicellular (intracellular but extracytoplasmic) [25].…”
Section: Life Cyclementioning
confidence: 87%
See 1 more Smart Citation
“…However, recent phylogenetic studies have shown closer proximity of Cryptosporidium with gregarine protozoan than with coccidia, because they have a feeding organelle and absence of apicoplast, which allowed their reclassification in the Gregarinomorphea class, Cryptogregaria subclass (KOH et al, 2013(KOH et al, , 2014CAVALIER-SMITH, 2014;HUANG et al, 2014;CLODE et al, 2015;ALDEYARBI;RYAN et al, 2016).…”
Section: Cryptosporidium: Taxonomic and Biological Aspectsmentioning
confidence: 99%
“…It is caused by species of the genus Cryptosporidium, in humans typically by C. parvum and C. hominis. The Cryptosporidium species belong to the phylum Apicomplexa and it has recently been proposed for the species to be reclassified as a member of the subclass of gregarina 5,6 . They are waterborne pathogens, and cryptosporidiosis has commonly been associated with disease in developing countries [7][8][9] .…”
mentioning
confidence: 99%